Examine middle school students' constructivist environment perceptions in Turkey: School location and class size - Yiğit, Nevzat; Alpaslan, Muhammet Mustafa; Cınemre, Yasin; Balcın, Bilal (Journal of Turkish Science Education, 2017)
This study aims to examine the middle school students’ perceptions of the classroom learning environment in the science course in Turkey in terms of school location and class size. In the study the Assessing of Constructivist Learning Environment (ACLE) questionnaire was utilized to map students’ perceptions of the classroom learning environment. The sample included 1882 students from Grades 6-8 randomly selected twenty schools in a northern province in Turkey. Data analysis revealed that there were significant differences between the perceptions of students from rural/urban schools and small/large classes. More specifically, students in small classes and rural schools reported their classroom learning environments more positively than those who were in large classes and urban schools in dimensions of thought provoking, collaboration, life relevance, concurrent learning and assessment, and bringing different viewpoints. Implications and future directions were discussed.
Keywords: Class size; constructivism; classroom learning environment; school location